Social Media Use and Self-assessed Vocabulary Knowledge among English Study Program Students - Rosalita Utami; Iis Sujarwati (Universitas Bengkulu, 2026)
This study investigated social media use and self-assessed vocabulary knowledge among English study program students. By conducting a survey of 82 students enrolled in an English study program, the questionnaire sought to reveal the frequency and types of students’ social media use as well as the self-assessed vocabulary knowledge of students. The data were analyzed using descriptive statistics. The findings indicated that students were moderately active on their social media for learning English, but had variations in the frequency. Further, Instagram and TikTok emerged as the most frequently used platforms for vocabulary acquisition. Even though the moderate engagement of social media use to learn vocabulary, the students demonstrated positive levels in self-assessed vocabulary knowledge. These findings suggest that social media use is an additional learning tool for the students, particularly for learning vocabulary. Therefore, the results of this study suggest that the integration of social media into the language curriculum may support vocabulary acquisition through interactive tasks or assignments. Keywords: Self-assessed Vocabulary, Self-assessed Vocabulary Knowledge, Social Media Use, Vocabulary Acquisition